2018
DOI: 10.1093/femsle/fny127
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9/sgRNA-mediated targeted gene modification confirms the cause-effect relationship between gyrA mutation and quinolone resistance in Escherichia coli

Abstract: Quinolones are broad-spectrum antibiotics that have been used for decades in treating bacterial infections in humans and animals, and subsequently bacterial resistance to these agents has increased. While studies indicated the relationship between gyrA mutations and bacterial resistance to quinolones, CRISPR/Cas9 was used in this study to investigate causal role of gyrA mutation in the quinolone resistance. In this study, 818 clinical Escherichia coli isolates were analyzed for gyrA mutations and their resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Recently, the clustered regularly interspaced short palindromic repeat (CRISPR) system and CRISPR-associated protein 9 (Cas9) were shown to provide adaptive immunity in prokaryotic defense systems, and the CRISP/Cas9 system has since been harnessed as a genome editing tool [18]. Attempts have been made to re-sensitize resistant E. coli using this system [19], [20]. In this study, we sequenced and annotated the genome of the carbapenem-resistant strain of Shewanella algae VGH117 and performed genome editing of 3 candidate genes using CRISPR/Cas9 and recE/recT recombinase to reverse the carbapenem resistance in S. algae .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the clustered regularly interspaced short palindromic repeat (CRISPR) system and CRISPR-associated protein 9 (Cas9) were shown to provide adaptive immunity in prokaryotic defense systems, and the CRISP/Cas9 system has since been harnessed as a genome editing tool [18]. Attempts have been made to re-sensitize resistant E. coli using this system [19], [20]. In this study, we sequenced and annotated the genome of the carbapenem-resistant strain of Shewanella algae VGH117 and performed genome editing of 3 candidate genes using CRISPR/Cas9 and recE/recT recombinase to reverse the carbapenem resistance in S. algae .…”
Section: Introductionmentioning
confidence: 99%
“…Mutation in gyr A 248, resulting in resistance to quinolone drugs has previously been reported in E. coli, and Salmonella isolates from both humans and animals 27 , 28 . One study screening 818 E. coli clinical isolates (77% resistant to nalidixic acid) from cows, chicken and pigs revealed that the most common nucleotide mutation site in gyr A was at position 248 (C → T), resulting in an amino acid change from serine to leucine at position 83 29 . Furthermore, this study used CRISPR/Cas9 to investigate the causal role of gyr A mutation in the quinolone resistance by inducing gyr A mutations in nucleotide 248 C to T and was able to successfully demonstrate the role of this mutation resulting in resistance to quinolone drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity for the absence of the referred resistance gene and prediction of lack of phenotypic resistance to the corresponding antimicrobial drug. tetA tetB (n = 1) % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 % 3 AuAmEn www.nature.com/scientificreports/ isolates (77% resistant to nalidixic acid) from cows, chicken and pigs revealed that the most common nucleotide mutation site in gyrA was at position 248 (C → T), resulting in an amino acid change from serine to leucine at position 83 29 . Furthermore, this study used CRISPR/Cas9 to investigate the causal role of gyrA mutation in the quinolone resistance by inducing gyrA mutations in nucleotide 248 C to T and was able to successfully demonstrate the role of this mutation resulting in resistance to quinolone drugs.…”
Section: Aac(6′)ib-crmentioning
confidence: 99%
“…10 Based on the CRISPR-Cas9 system, reported studies have been transformed E. coli with plasmids that coded sgRNAs to specifically cleave quinolone resistance gene and Extended-spectrum β-lactamases (ESBLs) resistance gene, respectively. 11,12 Together, using the CRISPR-Cas9 system to resensitize colistin-resistant E. coli by curing mcr-1-carrying plasmid is considered as a potentially effective method to resist the dissemination of colistin resistance genes.…”
Section: Introductionmentioning
confidence: 99%